ANALISA PERBANDINGAN MANAJEMEN WAKTU PERENCANAAN DAN PELAKSANAAN (STUDI KASUS: PADA PEMBANGUNAN ASRAMA PUTRA DI BOJONEGORO KAB. BOJONEGORO) - Setiawan, Agus; Lasmito, Lasmito; Nurin Sharvina, Ainun; Anam, Choirul; Rodhi, Syaifudin; Susilo, Edi (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
The success or failure of project implementation is often caused by poorly planned project activities, as well as ineffective control, resulting in inefficient project activities. This will cause delays and a decrease in the quality of work, and result in swelling of the cost of maintenance. Project management is carried out to manage the project from the beginning of implementation to the completion of the project. The case study in this study is the construction of the Male Dormitory Building as a means and infrastructure in teaching and learning activities in the Islamic boarding school environment located in Sumberagung village, Selorejo District, Blitar Regency. The CPM method is used to find out how long it takes for a project to be completed and look for possible acceleration of project implementation time. The purpose of this study is to determine the time efficiency reviewed from the method. The results of the time management analysis using the CPM method were obtained in a critical path for 723 working days, and the optimal time was obtained by being accelerated to 74 working days, which is 658 working days with an increase in costs of RP. 7,470,000,000,00;.